Pelatihan Pelayanan Anak Berkebutuhan Khusus - Ani Endriani; Nuraeni Nuraeni (Jurnal Dedikasi Madani, 2023)
AbstractThe purpose of this community service is to equip PAUD teachers in dealing with children with special needs. The target of this training is to provide 40 PAUD teachers from various PAUD institutions in DKI Jakarta province, students with special needs who really need special attention and treatment. Learning and treatment for classes with children with special needs are different from ordinary classes, so it requires teachers who are able to master classes, students, learning and special handlers. The hope of this activity is that with the knowledge they have about children with special needs, it is hoped that PAUD teachers will be able to provide maximum services according to the specificities of children to achieve optimal development.AbstrakTujuan pengabdian ini untuk membekali guru PAUD dalam menangani anak berkebutuhan khusus. Sasaran pelatihan ini diberikan pada guru-guru PAUD dari berbagai lembaga PAUD di propinsi DKI Jakarta sebanyak 40 guru, dengan siswa berkebutuhan khusus yang sangat memerlukan perhatian dan perlakukan yang khusus. Pembelajaran dan perlakuan bagi kelas yang memiliki anak berkebutuhan khusus berbeda dengan kelas biasa sehingga memerlukan guru yang mampu untuk menguasai kelas, siswa, pembelajaran serta penangan yang bersifat khusus. Harapan dari kegiatan ini  yaitu dengan pengetahuan yang dimiliki tentang anak berkebutuhn khusus  diharapkan guru PAUD mampu melakukan pelayanan yang maksimal disesuaikan dengan kekhususan anak untuk mencapai perkembangan yang optimal.